A Study of the Effective Lifetime of Aluminum Buckets Used in Blood Bank Centrifuges - Tafti, M. F.; Golestani, R.; Salari, M. (Engineering, Technology & Applied Science Research, 2017)
Rotating parts of blood bank centrifuges are under heavy mechanical cyclic stresses due to their centrifugal loading conditions. Estimating the effective lifetime for these parts is very important for their application. Providing safety requirements for these components is mandatory in blood transfusion centers (BTC). Failure occurs in the engineering parts for both loading conditions of steady and cyclic. The fatigue phenomenon is the main reason for mechanical failures at least in 90 % of fractures during operation. In this paper, the effects of fatigue caused by centrifugal loadings on aluminum buckets produced by the Iranian Sina Ebtekar Company (ISECo) are investigated experimentally. In this study, 48 aluminum buckets are chosen from a set of 500 buckets. The numbers of service of the samples are accounted for a period of 7 months. Finite element analysis, FEM, is done for an aluminum bucket and the relevant maximum stresses due to the rotating loads of centrifugation are determined. Analyzing the numerical results and using the fatigue, lifetime diagrams according to the number of operating cycles is presented for the samples. A good consistency is observed between the experimental and numerical results. Based on the results, a new correlation is presented for estimating the aluminum bucket’s lifetime made by ISECO.